Covid-19 And the Socioeconomic Impact on Self-employment in Sabah - Jia, Qi Cheong; Khairul Hanim Pazim; Lim, Beatrice Fui Yee; Noor Faziedah Chun Lee; Kasim Mansur (Universiti Malaysia Sabah, 2022)
The movement control order (MCO) and restrictions in economic activities issued in response to the COVID-19 outbreak has caused significant disruptions in employment. The impact of the pandemic has been greater for self-employed persons than for employed workers, as self-employed persons usually experience substantial obstacles in keeping their businesses alive. Studies on self-employment are thus very important for the nation since they are related to attempts to lessen the detrimental impact of covid-19 on self-employment. Entrepreneurs have overcome numerous challenges within the self–employment. This article investigates theCovid-19 impact on self-employment and small business income and sales. The paper also identify he salient beliefs that policymakers could target to reduce the problem faced by self-employed and small businesses. An online survey was conducted to see on how the self-employed are faring in the crisis covering their work patterns, earnings, concerns and expectations for the future. 185 respondents were collected. This paper suggest that policymakers can start thinking about self-employment policies for a post-COVID-19 economy now, because there is a need for more targeted measures to help disadvantaged self-employed persons stay in business.